Respuesta :
Answer:
[tex]y(t)\ =\ C_1e^{-2t}+C_2e^t\ -\ \dfrac{1}{2}[/tex]
Step-by-step explanation:
Given differential equation is
y"+y'-2y = 1
[tex]=>\ (D^2\ +\ D\ -\ 2)y\ =\ 1[/tex]
Hence, the characteristics is
[tex]D^2+D-2\ =\ 0[/tex]
[tex]=>\ D^2\ +\ 2D\ -\ D\ -2\ =\ 0[/tex]
[tex]=> (D+2)(D-1) = 0[/tex]
=> D = -2, 1
The general equation of the given differential equation is
[tex]y_c(t)\ =\ C_1e^{-2t}+C_2e^t[/tex]
Let's consider that
[tex]y_1(t)\ =\ e^{-2t}[/tex] [tex]y_2(t)\ =\ e^{t}[/tex]
[tex]y'_1(t)\ =\ -2e^{-2t}[/tex] [tex]y'_2(t)\ =\ e^t[/tex]
g(t) = 1
Wronskian can be given by,
W = y_1(t)y'_2(t) - y_2(t)y'_1(t)
[tex]=\ e^{-2t}.e^t\ -\ e^{t}.(-2e^{-2t})[/tex]
[tex]=\ e^{-t}\ +\ 2e^{-t}[/tex]
[tex]=\ 3e^{-t}[/tex]
Now, the particular integral can be given by
[tex]y_p(t)\ = \ -y_1(t)\int{\dfrac{y_2(t).g(t)}{W}dt}\ +\ y_2(t)\int{\dfrac{y_1(t).g(t)}{W}dt}[/tex]
[tex]=\ -e^{-2t}\int{\dfrac{e^t\times 1}{3e^{-t}}dt}\ +\ e^t\int{\dfrac{e^{-2t}\times 1}{3e^{-t}}dt}[/tex]
[tex]=\ -e^{-2t}\int{\dfrac{e^{2t}}{3}dt}\ +\ e^t\int{\dfrac{e^{-t}}{3}dt}[/tex]
[tex]=\ (-e^{-2t})(\dfrac{e^{2t}}{6})\ +\ (e^t)(\dfrac{e^{-t}}{-3})[/tex]
[tex]=\ \dfrac{-1}{6}\ -\ \dfrac{1}{3}[/tex]
[tex]=\ \dfrac{-3}{6}[/tex]
[tex]=\ \dfrac{-1}{2}[/tex]
Now,
[tex]y(t)\ =\ y_c(t)\ +\ y_p(t)[/tex]
[tex]=\ C_1e^{-2t}+C_2e^t\ -\ \dfrac{1}{2}[/tex]
Hence, the complete solution of the given differential equation is
[tex]y(t)\ =\ C_1e^{-2t}+C_2e^t\ -\ \dfrac{1}{2}[/tex]